Overpricing in Emerging Market Credit-Default-Swap Contracts : Some Evidence from Recent Distress Cases - Andritzky, Jochen (IMF Working Papers; Working Paper ;, 2005)
Since recent debt restructurings that constitute credit events have been more frequent than outright defaults, sovereign bond prices may not collapse during distress. In this case, the likely high recovery values after restructuring suggest that the cost of credit-default-swap (CDS) contracts to the buyer (as measured by CDS spreads) may be higher than warranted. We estimate the extent of such overpricing by using the cheapest-to-deliver (CTD) bond as a proxy for the recovery-value assumption.